Magnetic states in multiply-connected flat nanoelements - Bogatyrev, A.B.; Metlov, K.L. (Физика низких температур, 2015)
Flat magnetic nanoelements are an essential component of current and future spintronic devices. By shaping
an element it is possible to select and stabilize chosen metastable magnetic states, control its magnetization dynamics.
Here, using a recent significant development in mathematics of conformal mapping, complex variable
based approach to the description of magnetic states in planar nanoelements is extended to the case when elements
are multiply-connected (that is, contain holes or magnetic antidots). We show that presence of holes implies
a certain restriction on the set of magnetic states of nanoelement.